Prosedur Manajemen Kelas dan Pengaturan Ruang Kelas: Upaya Meningkatkan Efektivitas Proses Belajar Mengajar - Muhammad Qutbir Rabbani; Afina Afanin Nabila; Irmatus Sa’adah; Sapna Indah Nia; Khoirumansyah Khoirumansyah; Mu’alimin Mu’alimin (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the role of classroom management and classroom arrangement in improving the effectiveness of the teaching and learning process, especially in the context of the Character Education Strengthening Program (PPK). The research method used is descriptive qualitative with the research location at SD Negeri 1 Wonosobo, Central Java. Participants included teachers, principals, and students. The results of the study indicate that flexible and conducive classroom arrangements, such as the arrangement of tables and chairs according to learning activities, as well as physical factors such as good lighting and ventilation, can improve student focus and collaboration. Effective classroom management, including careful planning, clear communication, and an inclusive approach, has been shown to create a positive learning climate and increase student motivation and achievement. Obstacles such as limited facilities and diversity of student characters can be overcome through a democratic approach, teacher training, and collaboration with parents. Integration of character values in PPK through class agreements and teacher role models also strengthens student character formation. The conclusion of this study emphasizes the importance of synergy between classroom arrangements, classroom management, and PPK to create a holistic and effective learning environment.